An Examination of the Value of Bibliometric Research: Past Achievement and Future Prospects - Snyder, Herbert W.; Bonzi, Susan (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF